Major conundrums and possible solutions in DeFi insurance - Peng Zhou; Ying Zhang (Cardiff University, Cardiff Business School, 2025)
This paper empirically explores the early development of insurance projects in the decentralized finance (DeFi) industry, which is based on disruptive technologies like blockchain and smart contracts. A brief history of DeFi is narrated stressing four risks of DeFi (volatility risk, cyberattack risk, liquidity risk, and regulation risk) and its co-evolution with traditional finance. Then, first-hand evidence is collected from informed industrial practitioners by two semi-structured focus group discussions. Consensuses are reached on why the DeFi insurance market is underdeveloped and incomplete (the liquidity conundrum, the actuarial conundrum, the verification conundrum, the scale conundrum, the yield conundrum, the exploitation conundrum, the cybersecurity conundrum, and the regulation conundrum) and how the next generation of DeFi insurance can address these conundrums. Further evidence is obtained to quantify the importance of conundrums using Analytic Hierarchy Process (AHP). Building on the qualitative and quantitative findings, a prototypical model of DeFi insurance is proposed.
Keywords: G14; G22; G23; 330; Decentralized Finance; Insurance; Blockchain; Smart Contract; Focus Group; Analytic Hierarchy Process